Optimisation and rheological modelling of thermosonically extracted tropical fruit juice concentrates - Abdullah, Norazlin (2015)
This study aims to investigate the extraction of tropical fruit juice with assisted thermosonication treatment through optimisation and rheological modelling approach. Juice from the pink-fleshed guava, pink-fleshed pummelo and soursop was extracted using direct and indirect thermosonication methods by varying the intensity, time and temperature and compared to those extracted using water bath incubation. The main effects, and the 3D or 4D surface plots for each response were developed based on the factors that influenced the responses, where 3D surface plot contains of three axes for two variables and a response, while 4D surface plot explains three variables simultaneously with coloured surface to represent response values. The results indicated that the best extraction method for guava and pummelo juices were using the indirect thermosonication method with parameters of 1 kW, 55°C and 30 minutes and 2.5 kW, 54°C and 23 minutes, respectively. The direct thermosonication method at 10% amplitude and 55°C for 2 to 10 minutes was more suitable for the soursop juice. The steady-state flow test of pink-fleshed guava, pink-fleshed pummelo and soursop was studied for combination of different temperature and concentration. All the rheological data were then superimposed into a master curve using shear ratetemperature-concentration superposition technique to predict rheological behaviour at wider range of shear rate. The final equations show shear-thinning behaviour of pink-fleshed guava, pink-fleshed pummelo and soursop with flow behaviour index of 0.2217, 0.7507 and 0.6347, respectively. The influence of concentration on rheological behaviour of pink-fleshed guava, pinkfleshed pummelo and soursop juice concentrates was evaluated using existing models and their individual lines were shifted into a master curve using concentration-temperature principle to predict rheological parameters at wider concentration values. A new mathematical model could be applied to describe the effect of temperature on consistency coefficient and flow behaviour index of pinkfleshed guava, pink-fleshed pummelo and soursop. An expression for new mathematical model, which combined the Arrhenius and logistic sigmoidal growth models is proposed to alleviate problems of negative region of modelling the effect of temperature on consistency coefficient and flow behaviour index using the Arrhenius model alone, and due to the improvement of curve fitting (R 2≥0.99). In conclusion, tropical fruit juice extraction can be done efficiently with thermosonication treatment, where the combination of mild heat and cavitation effects of ultrasound functions to reduce juice yield, ascorbic acid content and total soluble solids content loss.